ln(x)=ln(x+4)-ln(3)

Simple and best practice solution for ln(x)=ln(x+4)-ln(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x)=ln(x+4)-ln(3) equation:


Simplifying
ln(x) = ln(x + 4) + -1ln(3)

Multiply ln * x
lnx = ln(x + 4) + -1ln(3)

Reorder the terms:
lnx = ln(4 + x) + -1ln(3)
lnx = (4 * ln + x * ln) + -1ln(3)
lnx = (4ln + lnx) + -1ln(3)

Reorder the terms for easier multiplication:
lnx = 4ln + lnx + -1 * 3ln

Multiply -1 * 3
lnx = 4ln + lnx + -3ln

Reorder the terms:
lnx = 4ln + -3ln + lnx

Combine like terms: 4ln + -3ln = 1ln
lnx = 1ln + lnx

Add '-1lnx' to each side of the equation.
lnx + -1lnx = 1ln + lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
0 = 1ln + lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
0 = 1ln + 0
0 = 1ln

Solving
0 = 1ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1ln' to each side of the equation.
0 + -1ln = 1ln + -1ln
Remove the zero:
-1ln = 1ln + -1ln

Combine like terms: 1ln + -1ln = 0
-1ln = 0

Divide each side by '-1'.
ln = 0

Simplifying
ln = 0

The solution to this equation could not be determined.

See similar equations:

| 35y^3-220y^2-175y=0 | | -6x-4*0=24 | | 20x^3+58x^2+42x=0 | | 36x^2-81= | | -8x+83=-85+16x | | -185-35x=0 | | 9y/11=-9 | | 14+3x=2+5x+5 | | 7x+8x=45-90 | | 6x+3=-45-2x | | 5(3x-2)=35+45 | | 2(h-1)=3(h+1) | | (2x-7/12)+x=(2x+7/2)+3 | | 5x^2+7x+95=0 | | .3333(5x-8)=3 | | y=2x+22/5 | | onethird(5x-8)=3 | | 5y=2x+22 | | -4x+13-2x=3x-11 | | 2x-5/3+5=8 | | -9m+m^2=0 | | (11b+9)(2b-3)=0 | | 2(x-7)-1=5(3x+1) | | 3x/5+2x=0 | | (t/8+5)=7 | | x=3x+7(x-8) | | -8=4(9-2)+4 | | 3x-x/8=30 | | 7-3r=r-4(5-2/5r) | | 6=4/5+5 | | -13=h-1 | | 0-4x+7=11 |

Equations solver categories